Filosofia da educação: uma história da disciplina no curso de Pedagogia da Universidade Federal de Minas Gerais [1968 1985] - Aurilane Mesquita Freitas (2016)
This research analyzes the historical setting of Philosophy of Education discipline in the training course of the Faculty of Education of the Universidade Federal de Minas Gerais (FaE/UFMG) between the years of 1968 to 1985. It investigates the discipline development process from its educational programs and legal and institutional reforms linked to the history of this institution and the social and political circumstances of the time. The theoretical and methodological foundation articulatesthe critical theory of Ivor Goodson curriculum and the Rodrigo Patto Sá Motta political historiography, besides dialogue with the newly developed research In:the field of history of the Disciplines. The documentary sources used were educational programs, curriculum structures, legal and institutional documents, mostly, available at the Research Center, Memory and Documentation (CEDOC/FaE/UFMG). The analysis of the legal parameters of the program and the course content madepossible to realize that its history is characterized, during the decades of 60 and 70, mainly, by recurrence in their conceptual approaches. There were subtle changes, more influenced by the proposals of curricular restructuring of the 80s.